2012
DOI: 10.1089/jamp.2011.0924
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Deposition and Clearance in Man: Comparison of a Bidirectional Powder Device and a Traditional Liquid Spray Pump

Abstract: The initial deposition following powder delivery was significantly larger in the ciliated mucosa of the upper and posterior nasal regions, whereas less was deposited in the lower regions. Overall nasal clearance of powder was slower initially, but due to retention in anterior nonciliated regions the overall nasal clearance after spray was slower.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
144
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(149 citation statements)
references
References 26 publications
1
144
0
Order By: Relevance
“…In contrast, EDS delivery takes advantage of a patient's own exhalation mechanics and the product design to overcome anatomic and physiologic restrictions that severely limit the delivery efficiency of traditional devices. This has been documented in several deposition studies [7][8][9], and future science group www.future-science.com opens up possibilities for finally achieving better topical activity in the nose, better absorption into the body, or even better penetration of drug into the central nervous system.…”
Section: In Your Own Opinion What Has Been the Most Important Milestmentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast, EDS delivery takes advantage of a patient's own exhalation mechanics and the product design to overcome anatomic and physiologic restrictions that severely limit the delivery efficiency of traditional devices. This has been documented in several deposition studies [7][8][9], and future science group www.future-science.com opens up possibilities for finally achieving better topical activity in the nose, better absorption into the body, or even better penetration of drug into the central nervous system.…”
Section: In Your Own Opinion What Has Been the Most Important Milestmentioning
confidence: 88%
“…But with traditional approaches, these protective functions impede efficient drug delivery. The drug is deposited mainly anteriorly [7][8][9][10][11]. To avoid this 'drip-out', people tend to wipe their noses or sniff the drug along the nasal floor and therefore a large fraction ultimately ends up being lost or swallowed instead of reaching the targeted areas higher up and farther back in the nose.…”
Section: In Your Own Opinion What Has Been the Most Important Milestmentioning
confidence: 99%
“…The nasal valve and the complex tortuous nasal geometry are among the most important hurdles for efficient nasal drug delivery into the systemic circulation ( Figure 1). 41,42 The nasal valve region is the narrowest point in the entire respiratory tract and is located about 2 cm into the nose, at roughly the location separating the anterior from the posterior nasal cavity. The anterior portion of the nasal cavity is a small region lined with squamous epithelium designed to protect the body from inhaled particles and toxic substances, properties which are not ideal for efficient drug delivery.…”
Section: Nasal Anatomy and Migraine Treatment Administrationmentioning
confidence: 99%
“…42 In order to achieve optimal uptake and optimal pharmacodynamics, medications must efficiently and reliably be deposited in the posterior nasal cavity beyond the nasal valve. 41 Because the posterior nasal cavity is difficult to reach, it is under-used as a site of drug administration. 39,[43][44][45] Liquid nasal sprays often fail to fully penetrate beyond the nasal valve, as inhalation tends to create negative pressure within the nasal cavity and narrow the nasal valve passage.…”
Section: Nasal Anatomy and Migraine Treatment Administrationmentioning
confidence: 99%
“…22 Addressing these administration obstacles, we recently reported a study in neurotypical adult males comparing response to an emotion sensitivity task after a single dose of either intranasal oxytocin 8IU or 24IU, intravenous oxytocin (1IU), or placebo in a double-dummy and double-blind crossover trial using a novel Breath Powered device shown to enhance deposition in intranasal sites targeted for nose-to-brain transport. 38,39 A single administration of intranasal 8IU oxytocinmodulated social cognition, whereas intravenous administration did not, despite comparable peripheral blood concentrations of oxytocin after intranasal and intravenous oxytocin administration. 40 This indicates that nose-to-brain transport, rather than transport across the blood-brain barrier via peripherally circulating oxytocin, influences social cognition.…”
Section: Introductionmentioning
confidence: 99%